A rotary radiation structure for microwave heating uniformity improvement. (August 2018) - Zhu, Huacheng; He, Jianbo; Hong, Tao; Yang, Qianzhen; Wu, Ying; Yang, Yang; Huang, Kama
Graphical abstract: Highlights: A novel cavity structure for uniform and efficient heating is developed. A time subsection method for physical continuous rotary situation is performed. The multiphysics model is verified by experiments. Thermal inhomogeneity problem in materials' different layers is analyzed. Abstract: A novel microwave heating method with rotary radiation structure has been proposed to improve heating uniformity. Through time division of the whole heating process, static heating assumption of each time step and temperature inheritance between time steps, a simulation model has been built and computed based on the finite element method combined with programming. A quantitative validation of simulation results has been performed with physical experiments. Heating uniformity and heating efficiency of the proposed method has been compared with those of two traditional methods, by which a potato slice is heated with a turntable and heated statically. The results show that the rotary radiation structure has an obvious superiority. What is more, influences of positions of the waveguide that feeds microwave and its placing directions of the proposed method have also been discussed.